Pengaruh Kualitas Layanan dan Lokasi terhadap Kepuasan Pelanggan di Toko Mona Fashion - Hanre K Sibagariang; Ances Sitohang; Dohar Sinaga; Toman Sony Tambunan (Pusat Riset dan Inovasi Nasional, 2025)
The aim of the research is to identify and analyze the influence of service quality and location on customer satisfaction. This type of research uses a quantitative approach, because the data to be processed is ratio data and to determine the magnitude of the influence between the variables studied with a sample of 170 people. Where the samples taken have been using products from the Mona Fashion store and this research uses a statistical tool, namely SPSS. The analysis technique used in the research is the validity test, reliability test and normality test. The results of the research can be concluded that service quality partially has a positive effect on satisfaction. customers. This is proven by the t-calculated value being greater than the t-table, namely 2,134 > 0.1506. With a significance level of 0.000 < 0.05, location partially has a positive effect on customer satisfaction. This is proven by the t-calculated value greater than in the t-table, namely 0.503 > 0.1506. With a significant level of 0.000 < 0.05, simultaneously service quality and location influence customer satisfaction at mona fashion store and there is no indication of multicollinearity in this model so the analysis results are considered valid.